Ultrasound Elastography in Children - Mirjam Močnik; Nataša Marčun Varda (Children, 2023)
Ultrasound elastography is a novel ultrasound technique, being extensively researched in children in the last decade. It measures tissue elasticity with the observation of tissue response after an external stimulus. From research to clinical practice, ultrasound elastography has evolved significantly in liver fibrosis evaluation in children; however, several other applications of the technique are available in both clinical practice and research environments. Practically, in children any organ can be assessed, including the brain in early ages, along with muscle and connective tissue elasticity evaluation, spleen, kidney, skin, lymphatic tissue, etc. The elastography method, age, body mass index and technical points should be considered when performing ultrasound elastography. This review highlights its vast potential as a diagnostic tool in the pediatric population, where ultrasound is a dominant imaging tool; however, the indications and exam protocol for its clinical use in several fields in pediatrics have yet to be elucidated.